The effect of electromagnet variation in the fuel line on engine performance and exhaust gas emissions - Swastika, Indra; Humami, Faris (Politeknik Negeri Lhokseumawe, 2025)
Improving combustion efficiency and reducing exhaust emissions remain key challenges in motorcycle engine development. This study experimentally evaluates the performance of an electromagnetic device using rubber and iron core materials, applied to both carburetor-based and fuel injection 125 cc motorcycle engines. The electromagnet was installed along the fuel line to enhance fuel ionization before combustion. The tests were conducted to measure engine power, torque, and exhaust emissions under both configurations. The results show that the electromagnet with an iron core significantly improved engine performance. In the carburetor system, power increased by 0.391 HP, from 9.929 HP to 10.320 HP with the torque reached 10.042 Nm. In the injection system, power rose to 9.894 HP and torque increased by 0.449 Nm to 10.234 Nm. Emission analysis revealed notable reductions of CO levels to 3.09% and HC to 1655 ppm in the carburetor engine, while in the injection engine, CO dropped to 1.32% and HC to 356 ppm. The electromagnet has the potential to be an effective solution in improving performance and reducing emissions. By helping ionize molecules before combustion led to improving fuel-air mixing which in turn increases engine performance and reduces emissions.